2018
DOI: 10.1248/bpb.b18-00082
|View full text |Cite
|
Sign up to set email alerts
|

SuHeXiang Essential Oil Inhalation Produces Antidepressant- and Anxiolytic-Like Effects in Adult Mice

Abstract: SuHeXiang (SHX) has been used to treat a wide range of diseases, including those related to the central nervous system. However, the effects of SHX on mood disorders are still elusive. This study aimed to investigate the effects of SHX essential oil on stress-induced depression of mice. In an acute stress-induced depression model, mice inhaled vehicle (1% Tween 80) for 10 min or 10% SHX for 10 or 30 min once daily for 12 continuous days. In the chronic mild stress (CMS)-induced depression model, mice were expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…51) Various depressive-and anxiety-like behaviors in mice model, like the decreased sucrose preference in SPT and the increased latency to feeding in NSF, could be induced by the chronic stress in mice model and can be alleviated by plant extracted compounds (i.e., sulforaphane, tea polyphenol). 15,23) To investigate whether brazilin also has the antidepressantlike and anxiolytic effects, CMS-induced depression mice model was carried out and behavioral tests (SPT, OFT and NSF) were conducted. The results showed that continuous 7-d administration of brazilin significantly increased sucrose preference of CMS-treated mice as well as fluoxetine treatment, Brazilin significantly decreased the latency to feeding (D) without affecting the total feeding in home cage (E) of chronically stressed mice during the NSF test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…51) Various depressive-and anxiety-like behaviors in mice model, like the decreased sucrose preference in SPT and the increased latency to feeding in NSF, could be induced by the chronic stress in mice model and can be alleviated by plant extracted compounds (i.e., sulforaphane, tea polyphenol). 15,23) To investigate whether brazilin also has the antidepressantlike and anxiolytic effects, CMS-induced depression mice model was carried out and behavioral tests (SPT, OFT and NSF) were conducted. The results showed that continuous 7-d administration of brazilin significantly increased sucrose preference of CMS-treated mice as well as fluoxetine treatment, Brazilin significantly decreased the latency to feeding (D) without affecting the total feeding in home cage (E) of chronically stressed mice during the NSF test.…”
Section: Discussionmentioning
confidence: 99%
“…8,52,53) Anti-oxidative and anti-inflammatory therapeutics have attracted more and more attention for development of antidepressants. 15,52) It was reported that several molecules, such as inducible nitric oxide (NO) synthase (iNOS), cyclooxygenases (COX1/COX2), nuclear factor kappa B (NF-κB), and NO, were related to the development of depression and antidepressant treatment. 8,9,54) The anti-oxidant and anti-inflammation and other pharmacological activities of Sumu and/or its extracts have been well investigated in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depression is one of the most devastating mental illnesses with substantial morbidity and high suicide rate, and it contributes to the global burden of disease resulting in serious consequences . The main problem in treating depression is that most of the antidepressants used in the clinic have significant limitations.…”
Section: Introductionmentioning
confidence: 99%